Application of Composting Technology to Reduce Organic Waste by Utilizing Black Soldier Fly (Hermetia illucens) Larvae - Ryzki Marcella Amalia Triadi; Mohamad Mirwan; Aulia Ulfah Farahdiba; Putri Redita Rositasari; Salsabila Prawardani (Nusantara Science and Technology Proceedings, 2022)
The larvae BSF (black soldier fly) can be used as an insect-based organic waste recycling technology. Not only for recycling organic waste, BSF larvae (black soldier fly) can also convert organic waste into a product in the form of compost. With so many waste problems, this technology is the most relevant way to deal with the problem. The purpose of this study was to examine the use of BSF (Black Soldier Fly) larvae in the composting process and to find out how much BSF (Black Soldier Fly) larvae were able to reduce organic waste. This study used an experimental method using 16 reactors containing 10000 larvae eggs in each reactor and using a variety of mixed waste. The variation used is the initial weight, in this study used an initial weight of 3 kg and 4 kg and treatment was carried out 2 times. The frequency of feeding was carried out every 3 days and then the weight reduction of the remaining waste in the reactor was measured after harvesting. The average percentage reduction in treatment 1 with an initial weight of 3 kg of waste is 18.25% while the initial weight of 4 kg of waste is 53.65%, different in treatment 2 the average percentage of waste reduction at an initial weight of 3 kg is 60 .25% and at 4 kg by 30.25%. The results of the compost will be compared with the quality standard of SNI 19-7030-2004, the results of the study show that treatment variation 2 at the initial weight of 3 kg of waste is closest to the quality standard based on the value of pH, water content, C-organic, N-organic and C ratio /N.